Training Enhancing the Potential of Integrated Gardens to Support Family Food and Nutritional Independence - Titik Juwariyah; Dewi Retno Puspitosari; Ary Kristijono; Diyan Wahyuningsih; Edi Santoso; Rizki Bahtiyar Ardyansah (Journal of Community Service for Health, 2026)
Introduction: The elderly are a vulnerable age group socially, economically, and health-wise, especially in rural and suburban areas. Based on data from the Ministry of Social Affairs of the Republic of Indonesia, approximately 40% of the total 25.67 million elderly in Indonesia are in the lowest socioeconomic status, which is categorized as vulnerable and potentially experiencing various physical and psychological problems. Methods: This community service activity carries the theme "Enhancing the Potential of Integrative Gardens as Supporters of Family Food and Nutrition Independence." This elderly empowerment program is a solution to prevent physical and psychological health problems and provides a platform for elderly people who have the potential to be economically productive. This program includes: 1) elderly-friendly gardening training, 2) small-scale livestock training, 3) local food management training, 4) marketing training, 5) elderly health training using medicinal plants around the house, and 6) group dynamics. This program is implemented in an integrated manner in the form of a Productive Elderly Class at the village hall. This community service has completed the first phase, namely training in creating an integrative garden with vegetable cultivation and raising catfish using used gallon jugs. Results: Participants' knowledge increased, from an average pretest score of 60.25 to 80 in the posttest. During the training, the elderly appeared enthusiastic and their productivity was evident, with the results of their planting media and catfish farming in used gallon jugs.